Genetic diversity and mating-type distribution within populations of Ascochyta rabiei in Turkey - ÖZER, GÖKSEL; BAYRAKTAR, HARUN; DOLAR, FATMA SARA (The Indian Journal of Agricultural Sciences, 2012)
Genetic diversity and mating-type distribution were studied within five populations of Ascochyta rabiei in Turkey. Of 122 isolates tested for mating type, 52.5% were identified as MAT 1-2 and 47.5% as MAT 1-1. Both mating types were observed in all populations, supporting the hypothesis of a randomly mating population. RAPD analysis was performed on 81 isolates of A. rabiei representing different pathotypes and geographic origins with 54 primers. Results of RAPD analysis clustered all isolates into nine groups an arbitrary level of 73% similarity. Total gene diversity (HT=0.221) was mostly attributable to diversity within populations (HS=0.213). Only 4% of the total variability were attributable to variation among populations. The results revealed low genetic differentiation and high gene flow among populations of A. rabiei in Turkey.